CARCASS AND NON-CARCASS COMPONENTS OF PELIBUEY EWES SUBJECTED TO THREE LEVELS OF METABOLIZABLE ENERGY INTAKE - Ruiz-Ramos, Jorge; Chay-Canul, Alfonso J.; Ku-Vera, Juan C.; Magaña-Monforte, Juan G.; Gómez-Vázquez, Armando; Cruz-Hernández, Aldenamar (Ecosistemas y Recursos Agropecuarios, 2015)
The aim of this study was to evaluate carcass and non-carcass components of adult Pelibuey ewes subjected to three levels of metabolizable energy intake (MEI). Eighteen 3-year-old Pelibuey ewes with body weight (BW) of 37.6 ± 4.0 kg and body condition of 2.5 ± 0.20 were randomly assigned to three groups of six ewes each in a completely randomized design. Ewes were housed in metabolic crates and fed three levels of MEI: low (L), medium (M), and high (H) for 65 d. Feed offered was adjusted every 15 d based on ewe BW. The MEI was 0.247, 0.472 and 0.532 MJ/ kgBW0.75d−1 for L, M and H levels, respectively. Data recorded at slaughter were weights of viscera, offal and carcass. Carcass was split at the dorsal midline into two equal halves, weighed, and chilled at 6°C for 24 h. The left half carcass was then divided into five cuts, each of which was dissected into fat, muscle and bone, and weighed separately. Hot and cold carcass weight and hot carcass dressing were greater for the H group than for the L group (p < 0.05). The weights of rib/flank and shoulder were different among groups (p < 0.05). Weights of empty rumen, liver, lungs and trachea, skin and internal fat were greater for the H group than for the L group (p < 0.05). A high level of MEI improves commercial dressing percentage due to increased lean meat and fat deposition with a lower proportion of bone in the carcass of adult Pelibuey ewes.